Association of ghrelin dynamics with beta cell function in Japanese subjects with normal glucose tolerance. (11th September 2019) - Murai, Norimitsu; Saito, Naoko; Kodama, Eriko; Iida, Tatsuya; Mikura, Kentaro; Imai, Hideyuki; Kaji, Mariko; Hashizume, Mai; Kigawa, Yasuyoshi; Koizumi, Go; Tadokoro, Rie; Sugisawa, Chiho; et al.
Abstract: Background: Ghrelin is involved in feeding regulation and energy metabolism and is also known to inhibit insulin secretion (β). However, few clinical studies have demonstrated the relationship between β and ghrelin dynamics. This study tested the hypothesis that, in oral glucose tolerance tests (OGTT), ghrelin dynamics are associated with β. Methods: Subjects were 1145 healthy individuals <40 years old who tested normal on the 75‐g OGTT. The following indicators and the ghrelin suppression ratio (GSR) during OGTT were calculated: insulin sensitivity (SI) [1/homoeostasis model assessment of insulin resistance, insulin sensitivity index‐Matsuda and 1/fasting insulin (1/FIRI)]; and β [Stumvoll first‐phase index (Stumvoll‐1), Stumvoll second‐phase index and insulinogenic index]. From nine combinations of SI and β, combinations that produce hyperbolic relationships were identified. Results: Stumvoll‐1 and 1/FIRI showed a hyperbolic relationship in nonobese subjects, and the product of Stumvoll‐1 and 1/FIRI was used as the disposition index (DI). When analyzed by BMI quartiles, post‐loading glucose and insulin levels at each time point increased from Q1 (low BMI) through Q4 (high BMI), whereas the DI, ghrelin levels at each time point, and GSR decreased from Q1 to Q4. On multivariate and bivariate analysis, GSR and DI were positive and independent, and fasting ghrelin and FIRI were negatively and independently correlated. Conclusions: Ghrelin dynamics were associated with beta cell function in subjects with normal glucose tolerance. Glucose intolerance in obesity may be due not only to insulin resistance but also to impaired beta cell function associated with abnormalities of ghrelin dynamics.